Building sustainability indicators in the health dimension for solid waste management - Tatiane Bonametti Veiga; Silvano da Silva Coutinho; Silvia Carla Silva Andre; Adriana Aparecida Mendes; Angela Maria Magosso Takayanagui
ABSTRACT Objective: to prepare a list of sustainability indicators in the health dimension, for urban solid waste management. Methods: a descriptive and exploratory study performed jointly with 52 solid waste specialists, using a three-steps Delphi technique, and a scale measuring the degree of importance for agreement among the researchers in this area. Results: the subjects under study were 92,3% PhD's concentrated in the age group from 30 to 40 years old (32,7%) and 51% were men. At the end of the 3rd step of the Delphi process, the average and standard deviation of all the proposed indicators varied from 4,22 (±0,79) to 4,72 (±0,64), in a scale of scores for each indicator from 1 to 5 (from "dispensable" to "very important"). Results showed the level of correspondence among the participants ranging from 82% to 94% related to those indicators. Conclusion: the proposed indicators may be helpful not only for the identification of data that is updated in this area, but also to enlarge the field of debates of the environmental health policies, directed not only for urban solid waste but for the achievement of better health conditions for the Brazilian context.